STUDY OF ISOTONICITY AND OCULAR IRRITATION OF CHLORAMPHENICOL IN SITU GEL - KURNIAWANSYAH, INSAN SUNAN; RUSDIANA, TAOFIK; ABNAZ, ZAHRA DZAKIRAH; SOPYAN, IYAN; SUBARNAS, ANAS (International Journal of Applied Pharmaceutics, 2021)
Objective: The objective of this study was to find out the isotonicity of chloramphenicol ophthalmic in situ gel and to know the irritating effect of its in the eyes of test animals, so it can be to maximize absorption of the drug in the eye, minimize drug loss before corneal penetration and safe to used. Methods: This study were started by making four aseptic formulations of in situ gel preparations with a comparison of the baseline concentrations of different Poloxamer 407 and HPMC, F1 (5: 0.45), F2 (10: 0.45), F3 (5: 1) and F4 (10: 1). Four aseptic of in situ gel preparations, followed by a qualitative isotonicity test using blood cells to see the comparison between control and test preparations, and ocular irritation test using the draize test method to determine the presence or absence of the irritation. Results: The results obtained from the isotonicity test showed that the four preparations have normal blood cells that similar with isotonic control solution; therefore, it can be said that the preparations have been made isotonic. The results of the ocular irritation test using the draize test method showed for each category, such as cornea, iris, conjunctiva and edema were zero. A zero value on the cornea indicates no ulceration or opacity, and the iris, conjunctiva and edema were normal. Conclusion: Chloramphenicol in situ gel are isotonic and do not cause irritation to the rabbit's eyes, so they are safe to use and the formulation can be used for further research until the final goal is obtained.